Taming Financial Development to Reduce Crises - Ben Naceur, Sami (IMF Working Papers; Working Paper, 2019)
This paper assesses whether and how financial development triggers the occurrence of banking crises. It builds on a database that includes financial development as well as financial access, depth and efficiency for almost 100 countries. Through estimation of a dynamic logit panel model, it appears that financial development, from an institutional dimension and to a lesser extent from a market dimension, triggers financial instability within a one- to two-year horizon. Additionally, whereas financial access is destabilizing for advanced countries, it is stabilizing for emerging and low income ones. Both results have important implications for macroprudential policies and financial regulations.